Development and validation of the Muslim Prayer Ability Scale (MPAS) - Mohd. Yusof, Nazri; Jasni, Muhammad Jasfizal; Musa, Ramli; Muhammad, Hasbullah (2021)
Introduction: Prayer is one of the pillars of Islam and a fundamental component of ibadah. Performing prayer would require individual fitness to form physical, verbal and cognitive tasks. The preparatory task before prayer includes cleansing of body, ablution, and proper clothing. Patients with diabetic foot problems may face difficulties in performing these tasks; hence, this study's objective is to develop and validate a new Muslim prayer ability scale. Method: Five experts each from orthopaedic, psychiatry, Islamic Revealed Knowledge and Heritage and Islamic philosophy of science were gathered to construct the domains and items for the new scale. The preliminary 23 item-scale was then administered to 212 diabetic foot patients in 2 hospitals (IIUM Medical Centre and Hospital Tengku Ampuan Afzan). Based on Construct validation analyses and factor loadings, 4 items were dropped because of poor reliability (low Cronbach’s alpha value). We established a 19-item scale to measure the Muslim prayer ability called the Muslim Praying Ability Scale (MPAS). Results: The reliability of the 19-item scale has a good Cronbach’s alpha value (0.79). Construct validity using exploratory factor analysis exhibit good factor loadings for all 19 items, and 5 components were extracted. The Kaiser-Meyer-Olkin (KMO) value was 0.72. The Exploratory Factor Analysis showed the 19 items of praying ability scale composed of five domains with three items in each domain. All the items showed good factor loadings of more than 0.5. The 5 identified domains are namely Preparation of praying (factor 1), Physical movement (factor 2), Spirituality (factor 3), Cognitive & Tayammum (factor 4) and Disturbance (factor 5). The individualized Cronbach’s alpha of each domain ranged from 0.67 to 0. 903. Conclusion: This study proved that the new MPAS is valid and reliable to be used as tools to measure prayer ability in diabetic foot patients.